Georgia Architectural and Historic Properties Survey of Pavo [003] Adams St. Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Pavo [003] Adams St. Quitman, Ga. December 1980. A one story rectangular plan with gabled and hip roof. Hip porch. Modern windows.ccc Asbestos siding. Brick piers. Fair condition. Date of Construction: c. 1915. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Pavo [003] Adams St. Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.11 MB (1,165,434 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)